Living kidney donors - a prospective study of quality of life before and after kidney donation - Garcia, Márcia Fátima Faraldo Martinez [UNESP]; Andrade, Luís Gustavo Modelli de [UNESP]; Carvalho, Maria Fernanda C. [UNESP] (Wiley, 2013)
Although the safety of living kidney donation has been well established, prospective studies examining the physical and psychosocial aspects of the donor's quality of life are still scarce. Thus, the purpose of this prospective work was to assess the quality of life of 50 consecutive donors before and after kidney transplantation. All donors were asked to respond to both a donor questionnaire and the short-form 36-item health survey (SF-36). Interviews were individually conducted before, three months after, and over one yr after transplantation. Donation was considered a positive experience by all patients and had no impact on any physical or psychosocial aspect of the donor's life. Improved self-esteem and better quality of life after donation were reported in 52% of the cases. All donors would donate again and encouraged donation. SF-36 data indicated improvement in post-donation mental and physical scores among living donors closely related to recipient. Overall, most donors had a positive experience, felt no changes in quality of life, experienced enhanced self-esteem, would donate again, and recommended donation. © 2012 John Wiley & Sons A/S.
Keywords: Kidney transplantation; Living donor transplantation; Nephrectomy; Open nephrectomy; Quality of life; adult; aged; clinical article; daily life activity; female; graft failure; graft recipient; health care system; health status; hospitalization; human; kidney donor; kidney graft; kidney transplantation; living donor; male; nephrectomy; personal experience; priority journal; prospective study; quality of life; self esteem; Short Form 36; social psychology; vein thrombosis; Adult; Aged; Cross-Sectional Studies; Female; Follow-Up Studies; Health Status; Health Surveys; Humans; Kidney Transplantation; Living Donors; Male; Middle Aged; Prognosis; Prospective Studies; Quality of Life